Utilizing Raspberry Pi Pico microcontroller board in teaching and training students - Duong, Ngoc Doan (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
This research aims to study and utilize a new kind of microcontroller, Raspberry Pi Pico, to create applications related to electronic and automation control to teach students in the university. First, the structure and function of the Raspberry Pi RP2040 microcontroller chip and Raspberry Pi Pico board were introduced in general. Second, the author introduces how to connect Raspberry Pi Pico to a computer and how to control and program it. Then, real applications using Pi Pico were developed to demonstrate interesting things that can be created with Pi Pico including turning the light on and off automatically using ADC and photoresistor, displaying the real-time clock and temperature values on an LCD, showing text and images on a TFT screen, and controlling Pico W via the internet. Those real demonstrations show that Pi Pico is an easy and interesting kind of microcontroller for students and people to use, to make real applications. It is worth learning and applying this interesting microcontroller board in students’ theses, projects, and future jobs.